Landscaping practices, community perceptions, and social indicators for stormwater nonpoint source pollution management. (November 2016) - Persaud, Ann; Alsharif, Kamal; Monaghan, Paul; Akiwumi, Fenda; Morera, Maria C.; Ott, Emily
Highlights: This study used social indicators to assess stormwater management. There is a lack of awareness about environmental regulations related to fertilizer use. The social dimensions is crucial in sustainable stormwater management. Abstract: This study sought to assess the relationship between regulatory and educational approaches to nutrient management and homeowner behaviors, perceptions, and knowledge of best management practices (BMPs). Fertilizers, and pesticides applied in excess by homeowners and landscapers can impair stormwater ponds and cause nuisance algae blooms, eutrophication and fish kills. They can also affect water quality in downstream creeks, and bays. To reduce the potential for nutrient-laden runoff to the aquatic environment, local and state governments passed different regulatory mechanisms that govern the use of BMPs and a fertilizer black out period. Interviews, surveys, and participant observation were used to gather quantitative and qualitative data in order to establish social indicator scores and evaluate knowledge and attitudes surrounding the fertilizer ordinance in a Master Planned community in Manatee County Florida. Results showed that most residents (69%) had not seen any materials related to the blackout period and lacked awareness of the components of the ordinance, including its restrictions on phosphorous and nitrogen applications and disposal of grass and landscape debris. The findings reveal the importance of social dimensions in sustainable stormwater management and suggest target areas for increasing awareness of the fertilizer ordinance and strengthening the link between social norms and environmental stewardship.